Using Scattergories Game in Teaching Vocabulary to Elementary School Students - Norma Yuliansyah; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2018)
This article aims to describe the use of Scattergories game in teaching vocabulary to elementary school students. Vocabulary is a basic component in mastering the four language skills; listening, speaking, reading, and writing. Therefore, vocabulary must be taught to children from elementary education. Elementary school students or called "young learner" have different characteristics with adults. They think concretely, act very actively and are very curious. Therefore, it is necessary to use the suitable vocabulary teaching techniques to compensate for the characteristics of the elementary school students, namely by using games, one of them is Scattergories game. By using Scattergories games, students can be active in the learning process and learn in a fun way.